2020
DOI: 10.4103/ijpc.ijpc_145_20
|View full text |Cite
|
Sign up to set email alerts
|

Patients'/Caregivers' perspectives on telemedicine service for advanced cancer patients during the COVID-19 pandemic: An exploratory survey

Abstract: Introduction: Novel coronavirus disease 2019 (COVID 19) has usurped human peace and mobility. The confinement of the population and the rising epidemic has disrupted the routine care for non-COVID-19 patients. Telehealth is a growing field, and its application in palliative care is seen as a solution to serve the population in this difficult crisis. Methodology: A exploratory survey was designed to assess the changes in the hospital-based practice of palliative care in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 17 publications
6
37
0
1
Order By: Relevance
“…Our study found that the telehealth model appears to have mitigated many of the adverse consequences of Covid-19, providing access to routine services. These findings are supported by other studies showing patient and caregivers satisfaction and the role of telehealth in facilitating continued access to care [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our study found that the telehealth model appears to have mitigated many of the adverse consequences of Covid-19, providing access to routine services. These findings are supported by other studies showing patient and caregivers satisfaction and the role of telehealth in facilitating continued access to care [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our study found that the telehealth model appears to have mitigated many of the adverse consequences of Covid-19, providing access to routine services. These ndings are supported by other studies showing patient and caregivers satisfaction and the role of telehealth in facilitating continued access to care [19,20].…”
Section: Discussionsupporting
confidence: 81%
“…Another survey conducted in a palliative care center demonstrated that 54% (n=27) of the participants rated the tele-consultation "satisfying". 7 A randomized control study reported patients who seek telemedicine avoided taking leave from work. 8 According to another study telemedicine reduces cost and saves time.…”
Section: Discussionmentioning
confidence: 99%
“…Binary multivariable logistic regression analysis was done to find the sociodemographic predictors of attitude towards tele consultation. Dependent variable was level of satisfaction and it was categorized as favorable (19-25) and unfavorable (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) considering the mean score of the participants. Favorable attitude score was coded as 1 and unfavorable score as 0.…”
Section: Methodsmentioning
confidence: 99%